An integrative review of attention biases and their contribution to treatment for anxiety disorders - Barry, Tom J.; Vervliet, Bram; Hermans, Dirk (Frontiers in Psychology, 2015)
Models of exposure therapy, one of the key components of cognitive behavioural therapy for anxiety disorders, suggest that attention may play an important role in the extinction of fear and anxiety. Evidence from cognitive research suggests that individual differences may play a causal role in the onset and maintenance of anxiety disorders and so it is also likely to influence treatment. We review the evidence concerning attention and treatment outcomes in anxiety disorders. The evidence reviewed here suggests that that attention biases assessed at pre-treatment might actually predict improved response to treatment, and in particular that prolonged engagement with threat as measured in tasks such as the dot probe is associated with greater reductions in anxious symptoms following treatment. We examine this research within a fear learning framework, considering the possible role of individual differences in attention in the extinction of fear during exposure. Theoretical, experimental and clinical implications are discussed, particularly with reference to the potential for attention bias modification programs in augmenting treatment, and also with reference to how existing research in this area might inform best practice for clinicians.